Whole School Approach on Social and Emotional Guidance among Rural Elementary Schools : Regular Teachers’ Involvement - Jessie Tnay, Koh Sing; Shahren Ahmad, Zaidi Adruce; Zaimuariffudin Shukri, Nordin; Omar, Haji Mahli; Chuo, Yew Ting (International Journal of Instruction (IJI), 2023)
This study explored the implementation of the whole school approach (WSA) on social and emotional guidance (SEG) in rural primary schools in Sarawak, Malaysia. Regular teachers (N = 2,532) in Sarawak responded to an electronic survey. The theory of planned behavior (TPB) and the socio-emotional guidance model were employed to explore the level of implementing the WSA on SEG among the respondents. Factors affecting the intention to be involved in SEG were also explored. This paper provides insights for policymakers and educational administrators to promote the social and emotional well-being of rural students in a developing country.